Early history of scapular fractures - Bartoníček, Jan; Kozánek, Michal; Jupiter, Jesse B (International orthopaedics, 2016)
The first to use the term Scapula was Vesalius (1514-1564) and thus it has remained ever since. Probably the oldest injured scapula, from 250 million years ago, was described by Chinese authors of a skeletal examination of a fossilised remains of a dinosaur Yangchuanosaurus hepingensis. In humans, the oldest known scapular fractures date back to the prehistoric and early historic times. In ancient times, a fracture of acromion was described in the treatises of Hippocrates. Early modern history of the treatment of scapular fractures is closely interlinked with the history of the French surgery. The first to point out the existence of these fractures were Petit, Du Verney and Desault in the 18th century. The first study devoted solely to scapular fractures was published by Traugott Karl August Vogt in 1799. Thomas Callaway published in 1849 an extensive dissertation on injuries to the shoulder girdle, in which he discussed a number of cases known at that time. The first radiograph of a scapular fracture was published by Petty in 1907. Mayo Robson (1884), Lambotte (1913) and Lane (1914) were pioneers in the surgical treatment of these fractures, followed in 1923 by the French surgeons Lenormat, Dujarrier and Basset. The first internal fixation of the glenoid fossa, including a radiograph, was published by Fischer in 1939.
Keywords: History, 16th Century; Arm Injuries; History, 17th Century; dějiny 20. století; Fracture Fixation, Internal; Scapula; poranění paže; vnitřní fixace fraktury; lopatka; History; History, 18th Century; dějiny 17. století; dějiny 16. století; History of treatment of scapular fractures; lidé; History, 20th Century; dějiny 18. století; Humans; dějiny 19. století; History, 19th Century; fraktury kostí; Scapular fracture; Fractures, Bone